A qualitative study of how Danish drug consumption rooms influence health and well-being among people who use drugs. Issue 1 (December 2016) - Kappel, Nanna; Toth, Eva; Tegner, Jette; Lauridsen, Sigurd
Abstract Background Drug use contributes to higher rates of morbidity and mortality among people who use drugs compared to the general population. In 2012, Danish politicians passed a law that allowed drug consumption rooms (DCRs) to operate; among the objectives were to improve the well-being of vulnerable citizens and to reduce the number of overdoses. Five Danish DCRs are currently being operated. This article presents results from a national investigation focused on assessing the impact of Danish drug consumption rooms on the health and well-being of DCR clients and factors facilitating the acceptance of DCR clients in order to improve their health and refer them onward to social and health service providers. Methods We conducted 250 h of participant observation in the DCRs, followed by in-depth qualitative interviews with 42 DCR clients and 25 staff members. Field notes and interviews were analysed and coded, and themes have been developed. Results DCR clients experienced a sense of social acceptance while inside DCRs. Members of staff conveyed a welcoming, non-judgemental attitude, and DCR clients were predominantly satisfied with the facilities. They prioritized forging relations with drug users so as to foster a sense of social acceptance within DCRs. The primary goal of staff members is to prevent overdoses by informing clients about strong drugs and by intervening in cases of intoxication. DCRs provide security to clients. In cases of health-related problems, DCR clients were referred to local health clinics. Members of the staff build bridges for DCR clients by guiding them towards drug treatment programmes and services in the social and the health sectors. Conclusions The study reveals a consistency between DCR clients and staff members with respect to appraisal of the importance of DCRs. Both clients and staff agreed that DCRs provide a safe haven in the environment in which DCR clients often live and that staff members' approach to clients with the intention of promoting acceptance clears the path for the prevention and treatment of overdoses and providing referrals to healthcare facilities, to drug treatment centres and to social services.